The influence of the competition phase and the result of the match on the competitive demands in football 5-a-side for the visually impaired - Gamonales, J. M.; Muñoz Jiménez, J.; Mancha-Triguero, D.; Ibáñez, S. J. (International Journal of Performance Analysis in Sport, 2021)
The use of inertial devices to assess load during competition makes it possible to objectively analyse football players` performance. The purpose of the present study was to analyse physical-physiological demands in footballers 5-a-side, as well as to ascertain the differences among the participating teams as a function of the competition phase (preliminary round/final phase) and result of the match (win/loss). The independent variables analysed were competition phase and result of the match, and the dependent variables were objective external kinematic load (distance, acceleration and deceleration), and neuromuscular load (player load), as well as the variables of objective internal load (heart rate). A descriptive analysis (M±SD), Student`s t-test and a general linear model were performed to discover the associations between the external and internal loads and the independent variables. The results show differences among the participating teams depending on competition phase and the result of the match. Moreover, the winning teams recorded a higher load in the preliminary round and the losing teams in the final phase. Thus, football 5-a-side for the visually impaired is a physically demanding sports discipline with a high degree of uncertainty.